Circulating Protectin D1 and Neutrophils Extracellular Traps in the Diagnosis and Progression of Acute Pancreatitis - Wu Z; Lu W; Zhang X; Xia Q; Zuo H; Guo X; Liu Y; Zhang F; Zhang X; Zhang L (Dove Medical Press, 2024)
Zhiyang Wu,1,* Wenjun Lu,2,* Xin Zhang,1 Qiaoying Xia,2 Han Zuo,2 Xi Guo,1 Yu Liu,1 Fan Zhang,3 Xin Zhang,4 Luyao Zhang2 1Department of Critical Care Medicine, Qilu Hospital (Qingdao), Cheeloo College of Medicine, Shandong University, Qingdao, Shandong, People's Republic of China; 2Department of Pathology and Pathophysiology, School of Medicine, Nanjing University of Chinese Medicine, Nanjing, Jiangsu, People's Republic of China; 3Department of Critical Care Medicine, Qilu Hospital, Cheeloo College of Medicine, Shandong University, Qingdao, Shandong, People's Republic of China; 4Department of General Surgery, Qilu Hospital (Qingdao), Cheeloo College of Medicine, Shandong University, Qingdao, Shandong, People's Republic of China*These authors contributed equally to this workCorrespondence: Luyao Zhang, Department of Pathology and Pathophysiology, School of Medicine, Nanjing University of Chinese Medicine, Nanjing, Jiangsu, People's Republic of China, Email zhangluyao@njucm.edu.cn Xin Zhang, Department of General Surgery, Qilu Hospital (Qingdao), Cheeloo College of Medicine, Shandong University, Qingdao, Shandong, People's Republic of China, Email 514557061@qq.comPurpose: Protectin D1 (PD1), a biologically active molecule derived from docosahexaenoic acid (DHA), plays a major role in the body's endogenous lipid-mediated inflammatory response. The study aims to explore the relationship between PD1, inflammatory response and the severity of acute pancreatitis (AP).Patients and Methods: Sixty consecutive AP patients within 72h of disease onset were enrolled as the study group, a further thirty healthy people were enrolled as the control group. General demographics collected at the time of enrollment. Serum PD1, Citrullinated Histone 3 (CitH3), myeloperoxidase-Deoxyribonucleic acid (MPO-DNA), tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6) level were measured in AP patients on enrollment day 0, day 1, day 3 and day 7. Meanwhile, the Acute Physiology and Chronic Health evaluation II (APACHE II) scores, Sequential Organ Failure Assessment (SOFA) scores were also evaluated on day 0, day 1, day 3 and day 7.Results: AP was severe in 29 patients (48.3%), moderately severe acute pancreatitis (MSAP) was found in 9 patients (15%), and mild acute pancreatitis (MAP) was found in 22 patients (36.7%). The level of PD1, CitH3 and MPO-DNA were statistically significantly higher in AP patients than in the healthy population. Serum PD1, CitH3 and MPO-DNA concentration increased with AP severity. In AP patients, PD1 has a strong linear association with TNF-α, CitH3 and MPO-DNA. The AUC for SAP predicted by PD1 was 0.938. The calculated cut-off point for prognosis SAP is 7.94 pg/mL. The AUC for infected pancreatic necrosis (IPN) predicted by PD1 was 0.836 and the cut-off point was 8.65 pg/mL. The AUC for organ failure (OF) predicted by PD1 was 0.719 and the cut-off point was 7.94 pg/mL.Conclusion: PD1 is associated with both the presence of AP and the severity of pancreatitis.Keywords: PD1, acute pancreatitis, CitH3, MPO-DNA, infected pancreatic necrosis, organ failure